Film Architecture and the Transnational Imagination Set Design in 1930s European Cinema - Bergfelder, Tim (Film Culture in Transition, 2007)
Film Architecture and the Transnational Imagination presents for the first time a comparative study of European film set design in the late 1920s and 1930s; based on a wealth of designers' drawings, film stills and archival documents, the book offers a new insight into the development and significance of trans-national artistic collaboration during this period. European cinema from the late 1920s to the late 1930s is famous for its attention to detail in terms of set design and visual effect. Focusing on developments in Britain, France, and Germany, Film Architecture and the Transnational Imagination: Set Design in 1930s European Cinema provides a comprehensive analysis of the practices, styles, and function of cinematic production design during this period, and its influence on subsequent filmmaking patterns.